1995
DOI: 10.1115/1.2822534
|View full text |Cite
|
Sign up to set email alerts
|

A Painting Technique to Enhance Pool Boiling Heat Transfer in Saturated FC-72

Abstract: A benign method of generating a surface microstructure that provides pool boiling heat transfer enhancement is introduced. Pool boiling heat transfer results from an enhanced, horizontally oriented, rectangular surface immersed in saturated FC-72, indicate up to an 85 percent decrease in incipient superheat, a 70 to 80 percent reduction in nucleate boiling superheats, and a ∼ 109 percent increase in the critical heat flux (CHF = 30 W/cm2), beyond that of the nonpainted reference surface. For higher heat flux c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(41 citation statements)
references
References 13 publications
2
39
0
Order By: Relevance
“…A number of studies have since explored various processing methods and geometric modifications for this structure, such as modulated porous copper coatings with periodic variations in layer thickness [2], a silver flake-based boiling enhancement paint [3], spray-coated alumina particulate layers [4], and porous graphite layers with randomly interconnected microscale pores [5,6], and observed significant enhancement of the heat transfer coefficient and critical heat flux (CHF).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have since explored various processing methods and geometric modifications for this structure, such as modulated porous copper coatings with periodic variations in layer thickness [2], a silver flake-based boiling enhancement paint [3], spray-coated alumina particulate layers [4], and porous graphite layers with randomly interconnected microscale pores [5,6], and observed significant enhancement of the heat transfer coefficient and critical heat flux (CHF).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to a smooth surface, the particle-coated surface decreased the incipience wall superheat by ~44% and increased CHF by ~36%. In a subsequent study, O'Connor and You [14] painted a mixture of silver flakes and epoxy over an aluminum surface to form a coating with 1 µm cavities; the incipience superheat was reduced by ~85% and CHF was increased by ~109%. Parker and El-Genk [15,16] studied nucleate boiling of HFE-7100 and FC-72, respectively, from porous graphite layers containing randomly interconnected microscale pores (60% porosity).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of porosity on boiling enhancement from dendritic copper surfaces, rather than particle-based coatings, El-Genk and Ali [20] found that the surface with the largest porosity produced the lowest nucleate boiling wall superheat. Besides the metallic coatings considered above, paintable porous coatings that use an epoxy binder were investigated by You and coworkers [21][22][23][24][25][26][27]. O'Connor and You [22] created a paintable coating that consisted of 3-10 lm silver flakes, Omegabond 101 thermal epoxy, and isopropyl alcohol.…”
Section: Introductionmentioning
confidence: 99%